Taxonomic revision of the genus Stenocephalum (Vernonieae, Asteraceae) - Dematteis, Massimiliano; Angulo, María Betiana (Phytotaxa, 2020)
The genus Stenocephalum Sch.Bip. (Vernonieae, Asteraceae) can be distinguished from the remaining South American members of the tribe by 4–11 florets per capitula, cylindrical involucres and cymose inflorescences. It can also be separated from other American genera of the tribe by the pollen grains, which are tricolporate and echinolophate, with a total of 29 lacunae arranged in a regular pattern, with a lacuna at each pole and without equatorial lacunae (type “C” pollen). At present, the genus comprises 7 species distributed from Mexico to Argentina. In this paper, all the entities recognized up to now are described and illustrated and one species is added to the group. The possible phylogenetic relationships of the genus are also discussed and the geographic distribution of most species is revised to include larger areas.